2001
DOI: 10.1080/20014091084227
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Glutamyl Transferase

Abstract: 1. Jousilahti P, Rastenyte D, Tuomilehto J. Serum gamma-glutamyltransferase, self-reported alcohol drinking, and the risk of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
746
1
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 982 publications
(791 citation statements)
references
References 292 publications
29
746
1
15
Order By: Relevance
“…The primary function of GGT is to supply intracellular support for the precursors of GSH, which is an important antioxidant. 1 Several studies demonstrated that an increase in serum GGT activity can be used as a marker for increased oxidative stress in humans. 2,10 It has been shown that GGT activity is directly related to the oxidative events, and plays an important role in the evolution of atheromatous plaque.…”
Section: Ggt Activity and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary function of GGT is to supply intracellular support for the precursors of GSH, which is an important antioxidant. 1 Several studies demonstrated that an increase in serum GGT activity can be used as a marker for increased oxidative stress in humans. 2,10 It has been shown that GGT activity is directly related to the oxidative events, and plays an important role in the evolution of atheromatous plaque.…”
Section: Ggt Activity and Oxidative Stressmentioning
confidence: 99%
“…GGT prepares precursor amino acid to intracellular glutathione (GSH) and catalyzes the first step in the degradation of extracellular GSH. 1 GSH is the most important nonprotein antioxidant of the cell. It has been reported that degradation of GSH may play a prooxidant role in selected conditions; low density lipoprotein (LDL) oxidation through GSH/GGT-dependent iron reduction has been suggested as an important mechanism in the pathogenesis of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In clinical practice, GGT is commonly used as a diagnostic test to assess liver dysfunction, and as a biological marker of excessive alcohol intake. 1,3,4 However, several recent epidemiologic studies have shown elevated GGT to independently influence morbidity and mortality from causes other than liver disease. Particularly, GGT was independently related to cardiovascular disease, [5][6][7][8][9][10][11][12] it correlated with most cardiovascular risk factors [13][14][15][16] and, more recently, an association with chronic kidney disease was found.…”
mentioning
confidence: 99%
“…A similar pattern of associations was observed in datasets from the Coronary Artery Risk Development in Young Adults (CARDIA) study [2], the Finland Multinational Monitoring of Trends and Determinants in Cardiovascular Disease (FinMONICA) study [3], the National Health and Nutrition Examination Survey (NHANES) [4], and in German women, but not men [5], leading us to search for new interpretations of serum GGT. Cellular GGT, found on the plasma membrane in most tissues [6], metabolises extracellular glutathione (GSH), the main intracellular antioxidant, allowing precursor amino acids to be reutilised for intracellular GSH re-synthesis [7]a process known as the 'γ-glutamyl cycle' (Fig. 1, left of the dotted line) [8].…”
mentioning
confidence: 99%